Chapter A new transplanting method of Posidonia oceanica (Linnaeus) Delile, 1813 plants - Bedini, Roberto (Proceedings e report, 2020)
The seabed of the port of Piombino was to be modified to allow the arrivals of cruise ships. The great problem to overcome was the presence of Posidonia oceanica (Linnaeus) Delile, 1813 meadows. Initially, the project was to remove and grind the plants of the meadow causing a considerable environmental damage. The Port Authority of Piombino asked the Institute of Marine Biology and Ecology to study an alternative project. Knowing the short results of the methods of replanting P. oceanica plant by plant we decided to transplant 340 clods of P. oceanica of 2 m2 to a nearby meadow.